Предмет: Алгебра,
автор: Sergio98
70/х^2-16 - 17/х-4 = 3х/х+4
Ответы
Автор ответа:
0
70/х^2-16 - 17/х-4 = 3х/х+4
70/(х-4)(х+4) -17/(х-4)=3х/(х+4)
70-17(х+4)=3х(х-4)
70-17х-68=3х^2-12х
3х^2+5х-2=0
х1=1/3
х2=-2
70/(х-4)(х+4) -17/(х-4)=3х/(х+4)
70-17(х+4)=3х(х-4)
70-17х-68=3х^2-12х
3х^2+5х-2=0
х1=1/3
х2=-2
Похожие вопросы
Предмет: Английский язык,
автор: irem2033
Предмет: Литература,
автор: bazenaevan
Предмет: Английский язык,
автор: dinislamovt
Предмет: Алгебра,
автор: Аноним
Предмет: Литература,
автор: Sophineko